2006
DOI: 10.1016/j.jcrs.2006.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes after accommodating intraocular lens implantation

Abstract: The Crystalens IOL provided better uncorrected near and distance visual outcomes than standard monofocal IOLs in all analyses performed. Patients perceived a greater accommodation than measured. Understanding why this occurred could lead to valuable advances in accommodating IOL technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…If 19 and the other was an experience report 20 ; 1 study by Claoué et al 21 and 1 study by Macsai et al 22 because they reported only uncorrected visual acuity data.…”
Section: Methodsmentioning
confidence: 99%
“…If 19 and the other was an experience report 20 ; 1 study by Claoué et al 21 and 1 study by Macsai et al 22 because they reported only uncorrected visual acuity data.…”
Section: Methodsmentioning
confidence: 99%
“…They also have an application in cosmetics, as well as, they are used for eye protection and healing of corneal lesions 14 . Thus there are PMMA based rigid lenses, soft lenses made of gel like plastic biomaterials and rigid gas permeable(RGP) lenses, constituted of hydrophobic plastic polymeric materials, used in treatment of presbyopia and severe astigmatism.…”
Section: Fig6: Titanium Based Dental Implant Ocular Lensesmentioning
confidence: 99%
“…The ability of the Crystalens HD to move forwards enables pseudophakic accommodation; this has been confirmed in several scientific studies using objective and subjective methods (see Figure 4). [1][2][3][4] Also according to the literature, the polyimide material of the haptics causes the IOL to grow quickly and firmly together with the capsular bag. For undisturbed and complete growth, it is important that the patient does not accommodate during the first 10 days after implantation.…”
Section: Mechanism Of Action Of the 'Accommodative' Crystalens Hdmentioning
confidence: 99%